Development of electronic student worksheets on junior high school students' descriptive text writing skills assisted by liveworksheets - Vina Aris Diana; Gallant Karunia Assidik (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2025)
This study aims to develop an Electronic Student Worksheet to improve the ability to write descriptive texts of junior high school students assisted by Liveworksheets. This study is a development research (R&D), with a research method that applies the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation, Evaluation. The subjects in this study were grade VII junior high school students in the city of Surakarta. Based on the results of the study, it can be seen that the form of Electronic Student Worksheet contains identity, open materials, activities or practice questions, evaluations, conclusions or feedback that are arranged regularly. The impact after using E-LKPD on the ability to write descriptive texts of junior high school students is 19.37. At an average value of the initial condition of students of 58.12 in the pre-test, an average value of 61.25 was obtained and for the post-test, a significant increase in value was obtained, namely 80.62.